2017
DOI: 10.1186/s12890-017-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefit of bosentan therapy in borderline or less severe pulmonary hypertension secondary to idiopathic pulmonary fibrosis—an interim analysis of results from a prospective, single-center, randomized, parallel-group study

Abstract: BackgroundNo drugs have been approved for the treatment of patients with pulmonary hypertension (PH) secondary to idiopathic pulmonary fibrosis (IPF), particularly those with idiopathic honeycomb lung. This study was conducted to investigate the long-term efficacy and safety of bosentan for PH based on changes in prognosis and respiratory failure.MethodsIPF patients with borderline or less severe PH and completely organized honeycomb lung were randomized (1:1) to bosentan or no treatment for PH for 2 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Although one RCT did report decreased all-cause mortality to end of study, its results were limited by a small sample size and high risk of bias. 26 The current findings of our pooled estimates might be explained in the following ways. 1) The development of IPF-associated PH can be explained by hypoxemia-induced vascular remodeling, IPF-specific hyperplasia and fibrosis of the elastic lamina of small pulmonary arteries, in situ thrombosis in small pulmonary arteries, intimal proliferation and fibrosis of the pulmonary venules, and various IPF-mediated cytokine effects.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although one RCT did report decreased all-cause mortality to end of study, its results were limited by a small sample size and high risk of bias. 26 The current findings of our pooled estimates might be explained in the following ways. 1) The development of IPF-associated PH can be explained by hypoxemia-induced vascular remodeling, IPF-specific hyperplasia and fibrosis of the elastic lamina of small pulmonary arteries, in situ thrombosis in small pulmonary arteries, intimal proliferation and fibrosis of the pulmonary venules, and various IPF-mediated cytokine effects.…”
Section: Discussionmentioning
confidence: 87%
“…One study had a significantly different all-cause mortality estimate than the others. 26 Even after excluding that study, 26 however, all-cause mortality did not differ significantly between the groups, although the heterogeneity decreased (HR, 0.99; 95% CI, 0.92, 1.06; P = 0.78; I 2 = 0%). We found no evidence of publication bias using Begg's (P = 0.266) and Egger's (P = 0.516) tests.…”
Section: Overall Survivalmentioning
confidence: 91%
See 1 more Smart Citation
“…16 In contrast, interim results from a small open-label study suggested bosentan improved hemodynamics and survival in patients with exercise or mild-moderate PH and IPF without parenchymal inflammation. 17 As the inclusion of only stable lung disease minimized confounding from respiratory exacerbations, it was suggested this may more accurately reflect the effect of bosentan on the pulmonary vasculature.…”
Section: The Endothelin-1 Pathwaymentioning
confidence: 99%
“…However, two drugs appear to be somewhat effective, namely the dual (ET A and ET B ) ET receptor antagonist bosentan and the selective ET receptor antagonist ambristan. However, their efficacy is restricted by their limited ability to penetrate tissue ( 37 - 39 ). Expression of ET-1 is mainly detected in the ECs of the pulmonary artery and may lead to intimal fibrosis and thickening of the media.…”
Section: Endothelin-1mentioning
confidence: 99%